2017
DOI: 10.4093/dmj.2017.41.2.146
|View full text |Cite
|
Sign up to set email alerts
|

A Cutoff for Age at Menarche Predicting Metabolic Syndrome in Egyptian Overweight/Obese Premenopausal Women

Abstract: Previous studies showed that early age at menarche is associated with increased risk of metabolic syndrome. However, the definition of early menarche at these studies was based on background data in the communities at which these studies was carried on. The aim of this work is to determine a cutoff for age at menarche discriminating presence or absence of metabolic syndrome in overweight/obese premenopausal women. This study included 204 overweight/obese women. Metabolic syndrome was defined according to NCEP-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 19 publications
3
4
0
Order By: Relevance
“…In this present study, a high frequency of EM was identified among MUH adolescents with adequate and high BMI, and among those who were between 10 and 14 years old. These findings are relevant, since several authors have pointed to a trend of reduction in the age at menarche in recent decades, which can be justified by important changes in body composition that occur during puberty [35,36,8]. In our data, among MUH adolescents, the significant correlation found between the age at menarche and body variables, such as BMI and BF%, corroborate this hypothesis.…”
Section: Discussionsupporting
confidence: 88%
“…In this present study, a high frequency of EM was identified among MUH adolescents with adequate and high BMI, and among those who were between 10 and 14 years old. These findings are relevant, since several authors have pointed to a trend of reduction in the age at menarche in recent decades, which can be justified by important changes in body composition that occur during puberty [35,36,8]. In our data, among MUH adolescents, the significant correlation found between the age at menarche and body variables, such as BMI and BF%, corroborate this hypothesis.…”
Section: Discussionsupporting
confidence: 88%
“…9 For metabolic syndrome, reaching menarche at age #12.25 years showed a higher sensitivity and negative predictive value in overweight/obese girls. 47 An AAM #11 years was associated with a higher risk for premature menopause. 11 In a Norwegian study, AAM !13 years was associated with a shorter duration of reproductive years.…”
Section: Discussionmentioning
confidence: 98%
“…The early menarche may be linked with increased harmful substances in the environment, especially related to exogenous hormone‐like substances through food additives and synthetic chemicals 15,16 . Early menarche might also be related to a variety of diseases including cardiovascular diseases, gynecological tumors, type 2 diabetes and gestational diabetes 17–20 . Studies also showed that age of menarche is associated with female fertility, 4,21,22 but no study has reported the relationship between the age of menarche and MA.…”
Section: Discussionmentioning
confidence: 99%
“…15,16 Early menarche might also be related to a variety of diseases including cardiovascular diseases, gynecological tumors, type 2 diabetes and gestational diabetes. [17][18][19][20] Studies also showed that age of menarche is associated with female fertility, 4,21,22 but no study has reported the relationship between the age of menarche and MA. Our study found that the age of menarche is not related to the occurrence of chromosome numerical abnormalities in patient group less than 30 years old, while in patients whose age are more than 30 years old and whose age of menarche are more than 12 years, the occurrence of chromosomes numeric abnormalities may be lower.…”
Section: Relationship Between Patient's Age Age At Merchant and Chromentioning
confidence: 99%